Promoting effect of pomegranate peel extract on second-degree burn wound-healing through VEGF-A and TGF-β1 regulation. Issue 3 (May 2022) - Zhang, Li; Yang, Renhua; Hu, Yangyang; Yang, Yan; Zhang, Xiaochao; He, Bo; Shen, Zhiqiang; Yang, JianYu; Chen, Peng
Graphical abstract: Highlights: After many experimental explorations, we strictly controlled the burning time of burn fuel and duplicated the minipig second-degree burn model by open fire, which was similar to the pathological development of clinical burn patients. PPE showed a significant promoting effect on minipig second-degree burn model, which might be associated with the upregulation of the protein and gene expression levels of VEGF-A and TGF-β1. PPE had therapeutic effects in an experimental minipig second-degree burn model. The results rationalize further investigation into the clinical use of PPE in the treatment of burns or scalds. Abstract: Pomegranate peel extract (PPE), a polyphenolic compound derived from pomegranate, has been widely concerned for its anti-oxidant, anti-inflammatory, and bacteriostatic effects. The potential therapeutic effect of PPE on burn injury was investigated, and its possible mechanisms were explored. Minipigs with second-degree burn were treated with PPE, Jing Wan Hong, and silver sulfadiazine. Hematoxylin–eosin (HE) staining was performed to detect burn severity, and then biological tissues were biopsied on days 0, 7, 14, 21, and 28 after administration. Immunohistochemistry, western blot, and real-time polymerase chain reaction (RT-PCR) were used to detect the protein and mRNA expression levels of VEGF-A and TGF-β1 in skin tissues after treatment with PPE. Furthermore, the skin wound healing at different time points was monitored by macroscopic observation. HE showed that after 28-day PPE treatment, the morphology of the skin tissue showed a significant improvement. Macroscopic data monitoring indicated that the decrustation and fur growing time was shortened. Meanwhile, the rate of wound healing increased after PPE treatment. The combination of immunohistochemistry, western blotting, and RT-PCR showed that after PPE treatment, expression of VEGF-A and TGF-β1 increased sharply on day 7, maintaining a high level until day 14, showing a downward trend on day 21, and approaching normal levels on day 28. However, in the model group, the protein and mRNA expression levels of VEGF-A and TGF-β1 increased on day 28 after burn injury, which was a slow process. Results indicated that compared with the model group, the peak expression level of VEGF-A and TGF-β1 was earlier, which was consistent with decrustation, shortening of fur growing time, and improvement of wound healing rate in minipig second-degree burn model. PPE showed a significant promoting effect on minipig second-degree burn model, which might be associated with the upregulation of the protein and gene expression levels of VEGF-A and TGF-β1.